EVALUASI CIPP (Context-Input-Process-Product) PROGRAM ASI EKSKLUSIF SEBAGAI UPAYA PENURUNAN STUNTING DI BANTARBOLANG KABUPATEN PEMALANG - Ardiana Priharwanti (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2022)
Indonesia has faced. Based on the Nutrition Status Monitoring (PSG) for the last three years, short toddlers have the highest prevalence compared to other nutritional problems such as undernutrition, thinness, and even obesity. The prevalence of short toddlers has fluctuated from 2015 to 29.0%, decreased in 2016 to 27.5% and increased in 2017 to 29.6% (Kemenkes RI, 2018). And based on 3 Basic Health Research (Riskesdas) data, it shows that the proportion of stunting in children under five with short and very short nutritional status in Indonesia has decreased from 37.2% in 2013 to 30.8% in 2018 (Riskesdas, 2018). Based on the results of a preliminary study conducted at the Pemalang District Health Office, every year there are 10 villages that become stunting loci in each sub-district. In 2021 there are 40 villages that are loci of stunting and the achievement of the Exclusive Breastfeeding program is still low, only reaching 16.3% of the applicable provisions (Kemenkes RI, 2018). Method. This study uses digging deeper information related to how the implementation of the exclusive breastfeeding program as part of specific nutrition in the Scaling Up Nutrition program in Pemalang Regency through the CIPP (context-input-process-product) evaluation approach. The main informant was the Head of the Health Office in Pemalang Regency as the main informant, PKM Health Promkes as a companion informant and the Lokus Health Center, Village Midwife, Cadre, and Ms. Toddler as triangulation informants. Evaluation of the CIPP (context-Input-Process-Product) exclusive breastfeeding program in Bantar Bolang through in-depth interviews with informants obtained the following information. Results. Pemalang Regency also has programs other than exclusive breastfeeding, namely toddler class, stunting toddler class, pregnant women class, examination of pregnant women, children's posyandu, youth posyandu as an effort to prevent from the start, surveillance, tracking stunting toddlers, giving PMT to pregnant women, giving PMT to toddlers. , education for children's growth and development, weighing, measuring height, giving vitamins, and nutritional counseling. In terms of existing facilities and infrastructure and available funding, Pemalang Regency has not yet reached the target, there are several shortcomings. In addition, the parenting pattern that occurs in the Bantar Bolang community is still not appropriate so that the implementation of exclusive breastfeeding is still not optimal. From the results of research related to the evaluation of exclusive breastfeeding programs through CIPP indicators, it is necessary to strengthen the commitment and coordination of all parties and multi-sectors. In addition, it is necessary to strive for periodic program monitoring and sustainable assistance so that the achievement of exclusive breastfeeding programs as a form of specific nutrition programs in stunting management can be achieved.